RED BREAST SYNDROME (RBS) ASSOCIATED TO THE USE OF POLYGLYCOLIC MESH IN BREAST RECONSTRUCTION: A CASE REPORT - Mayer, H F; Perez Colman, M; Stoppani, I (Acta chirurgiae plasticae, 2020)
Some patients undergoing breast reconstruction with acellular dermal matrices (ADMs) develop postoperative erythema overlying their ADM grafts named red breast syndrome (RBS). To the best of our knowledge this entity has never been related to the use of a synthetic mesh. We present a case of a 61-year-old patient who underwent bilateral nipple-sparing prophylactic mastectomy because of BRCA-1 gene mutation. The patient was reconstructed with a direct-to-implant approach, and the implants were covered with a polyglycolic acid mesh. Twenty days after the reconstruction, she presented with a blanching erythema of both reconstructed breasts without signs of infection on the area covered by the mesh. The patient denied symptoms like fever or tenderness and presented with no clinical signs of infection. Her laboratory tests were within normal range. We decided to watch and wait. The patient continued strict controls in the outpatient setting. Gradually, the erythema begun to disappear and it resolved spontaneously. RBS has only been described with the use of ADMs, but since in this case the mesh was made of polyglycolic acid, we suggest RBS should be considered either with the use of biological or synthetic meshes. The importance of its differential diagnosis resides in distinguishing it from an infection.
Keywords: Breast Implantation; implantace prsní náhrady; Humans; lidé středního věku; chirurgické síťky; Surgical Mesh; Female; breast reconstruction; lidé; Breast Implants; Polyethylene Glycols; prsní implantáty; mamoplastika; polyglycolic acid mesh; Breast Neoplasms; mastektomie; ženské pohlaví; Middle Aged; erytém; polyglactin mesh; nádory prsu; Breast cancer; red breast syndrome; polyethylenglykoly; Erythema; Mastectomy; Mammaplasty